Ischemic stroke of unknown etiology in a young woman - Calvo-Romero, José María (2004)
Ischaemic stroke (IS) in young adults is relatively infrequent. However, approximately 10% of first IS may occur in patients 45 years old or younger. Principal causes of IS in young adults are cardiogenic or noncardiogenic embolism, atherosclerosis, arterial dissection, drugs abuse (cocaine and anphetamine), vasculitis, hypercoagulable states, dural sinus thrombosis and migraine. About a third of cases of IS in young adults may not have an identified cause. We describe a 39-year old female with an IS of unknown etiology.